Socially Responsible Human Resource Management: SLR - Indri Safitri; Sopiah Sopiah (Jurnal Publikasi Ilmu Manajemen, 2023)
The purpose of this SLR is to analyze Socially Responsible Human Resource Management using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method with data obtained from Diva Portal, Sciencedirect, and Google Scohlar (2018-2023). After utilizing the inclusion and exclusion criteria, 36 journals were reviewed from a total of 304 journals. The findings of this study show that socially responsible HR in the workplace will benefit the surrounding environment and the company. To maintain a positive work environment, corporate responsibility for employee well-being is considered important. Providing facilities to employees, welfare programs, a safe and healthy work environment, as well as career development support is the implementation of Corporate Social Responsibility (CSR), where companies are responsible both socially and environmentally. It is a way to protect the environment, contribute to the company, and consider social, cultural, and economic considerations when running a business.